Treatment outcome in patients with severe acute malnutrition managed with protocolised care at malnutrition treatment corner in Rajasthan, India: a prospective observational study (quasi-experimental) - Nagar, Rajendra P.; Nagar, Teena; Gupta, Brahm D. (International Journal of Research in Medical Sciences, 2016)
Background: Malnutrition is rampant in paediatric age group. It is responsible for high morbidity, mortality and serious long term sequelae. In addition to critical care, a nutritional therapy followed by nutritional rehabilitation is a very important aspect for these children. Optimal management of these acutely ill children and a good outcome depends on an evidence based regimen of care. Methods: Total 75 cases were enrolled in the study and nursed in malnutrition treatment corner and were fed in appropriate composition and quantity as per Indian academy of pediatrics guidelines (initial and rehabilitation phase; F75, F100 and staple food). All children were assessed daily for weight gain, improvement in clinical status, feeding problem, compliance with the treatment and improvement in the appetite. Results: Out of 75 patients 63 (84%) patients were discharged. Dropout rate and mortality rate was 16% and 1.3% respectively. Majority patients were admitted for two weeks with mean duration of stay being 14.13 ± 9.1 days. Weight gain was good in 45, moderate in 22 and poor in 4 patients while 4 patients had weight loss during malnutrition treatment corner stay. Rate of weight gain was good in initial two weeks but as stay increased, rate of weight gain decreased in 3rd and 4th week with mean weight gain of 12.12±7.67 gm/kg/day. Twenty nine patients came for follow up after discharge and among them, 15(51.7%) patients had poor rate of weight gain, 9(31%) had moderate and 2 (6.89%) patients had good rate of weight gain whereas 3 patients had weight loss on follow up. Conclusions: Severely malnourished children have a better weight gain and improvement in nutritional status while receiving protocolised care in malnutrition treatment corner, which results in faster recovery because it is well accepted and better tolerated. Hospital based management of these children in specialised feeding centre is very important for regaining lost weight.